Specific issues of assessment of helicopters security at the test stage - Televnyi , Ihor; Kozyr , Anton; Open’ko, Pavlo (Social Development and Security, 2021)
The process of testing any military aircraft, including helicopters, is to obtain the parameters (flight characteristics) that characterize this sample, and compare them with the parameters specified in the request for proposal. One of the key requirements for the protection system of modern helicopters is to reduce their thermal visibility, which is successfully implemented through the installation of screen-exhaust devices. The main characteristics of screen-exhaust devices contain a range of parameters and factors that not only require a comprehensive approach to assessing their effectiveness, but also constantly changing in the light of new developments in this area. Therefore, the question of improving the methods of assessment of the subsystem of screen-exhaust devices at the stage of testing the helicopter is quite relevant. Assessment of compliance of the helicopter with the installed screen-exhaust devices to the requirements of the tactical and technical task, at the testing stage, is impossible without a separate method, the use of which will provide a unified approach to determining the effectiveness of protection at pre-design and early design stages of development (modernization) also when testing protection systems of modernized and newest models of helicopter equipment. Many scientific researches and publications, both in Ukraine and abroad, have been paid attention to the problem of assessing the security of helicopters by reducing thermal visibility. But existing approaches do not fully take into account modern protection systems, such as screen-exhaust devices, which limits their use in testing new and upgraded models of helicopters. Given the current development of technology, there is a logical question of assessing the security of helicopters, taking into account the contribution of the subsystem of screen-exhaust devices of the protection system at the stage of their testing. The article analyzes the main components that determine the order of selection of criteria for evaluating the effectiveness of the helicopter protection system, taking into account the contribution of the subsystem of screen-exhaust devices. The analysis of the hierarchical structure of the helicopter, presented in the form of a complex technical system, which consists of elements that determine its properties. Ways to improve the methods of assessing the contribution of screen-exhaust devices to the overall protection system of the helicopter during the tests are proposed. According to the research results, a method of helicopter security assessment is proposed taking into account the contribution of the screen-exhaust device subsystem of the protection system, which allows to determine the weakest properties of the subsystem, assess its overall level, characterized by a set of indicators and develop measures to improve helicopter security.